Electrochemical Characterization Techniques for Performance Optimization in Dye-sensitized Solar Cells: A Narrative Review - Purnomo, Agung; Aziizudin, Achmad; S, Arbye; Yogiswara, Cahyo Wibi; Halim, Dimas Ardiansyah; Putra, Setya Drana Harry (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
Dye-sensitized solar cells (DSSCs) offer advantages such as low production costs, simple fabrication methods, and reduced toxicity compared to silicon-based solar cells, although their efficiency remains a major limitation. The aim of this review is to discuss the fundamental principles of DSSCs and evaluate the electrochemical techniques used to optimize their performance. The method employed is a narrative literature review, allowing the author to synthesize relevant literature from various sources. Current-voltage (I-V) measurements and electrochemical impedance spectroscopy (EIS) are identified as the primary tools for assessing DSSC efficiency and quality. The findings indicate that I-V measurements provide critical metrics such as efficiency and fill factor, while EIS helps identify charge transfer resistance and improves cell stability. Techniques such as voltammetry and Tafel polarization plots offer additional insights into catalytic activity and diffusivity. This review underscores the importance of electrochemical characterization in supporting efficiency improvements and the development of new materials, with EIS playing a key role in modelling cell morphology through equivalent circuit analysis.